A viral movement protein as a nuclear shuttle. The geminivirus BR1 movement protein contains domains essential for interaction with BL1 and nuclear localization. - Sanderfoot, A A (1996)
For the nuclear replicating bipartite geminiviruses such as squash leaf curl to systemically infect the host requires the active participation of two virus-encoded movement proteins, BR1 and BL1. These act in a cooperative manner to transport the viral single-stranded DNA genome from its site of replication in the nucleus to the cell periphery (A.A. Sanderfoot, S.G. Lazarowitz [1995] Plant Cell 7: 1185-1194). We have proposed that BR1 functions as a nuclear shuttle protein, transporting the viral single-stranded DNA to and from the nucleus as a complex that is recognized by BL1 for movement to adjacent cells. To further investigate this, we expressed BR1 mutants known to affect viral infectivity in Spodoptera frugiperda insect cells and Nicotiana tabacum L. cv Xanthi protoplasts and found these to be defective in either their nuclear targeting or their ability to be redirected to the cell periphery when co-expressed with BL1. Translational fusions to beta-glucuronidase and alanine-scanning mutagenesis further demonstrated that the C-terminal 86 amino acids of BR1 contains a domain(s) essential for its interaction with BL1 and identified two nuclear localization signals within the N-terminal 113 residues of BR1. These nuclear localization signals were precisely located within distinct 16- and 22-peptide segments of BR1. These studies support and extend our model for squash leaf curl virus movement, showing that BR1 has a domain structure, with an N-terminal region required for nuclear targeting and a C-terminal region required for its interaction with BL1.